Method verification and quantification of nimetazepam in erimin 5 using reverse phase HPLC - Bukhary, Aiman Arif Mohamed (Universiti Sains Malaysia, 2016)
Erimin 5 is a brand name of nimetazepam that can be found in the form of tablets and powder. Nimetazepam is the active ingredient of Erimin 5. The nimetazepam is one the benzodiazepines listed in the Dangerous Drugs Act ( 1952). The Erimin 5 is used to treat for short term severe insomnia in patients who had difficulties in falling asleep or maintaining sleep. This drug is commonly abused in Malaysia since its appearance in illicit drug markets in middle I 980's due to it wide availability and low price. Many samples of Erimin 5 were submitted to the forensic laboratories for analysis. Prior to the analysis, standard methods shall be verified if there is a change in operators, instruments, chemicals, or site of analysis. In this research, the method verification of a validated reverse phase high perfonnance liquid chromatography (RP-HPLC) method was conducted by looking at five parameters namely selectivity and specificity, linearity, limit of detection (LOD), accuracy by recovery, and precision. The results were as follows, selectivity: a distinct narrow peak of nimetazepam, limit of detection (LOD): 0.002 mg/mL, linearity: R2 value was I, accuracy: more than 80% for 0.1 mg/mL, 0.2 mg/mL, and 0.3 mg/mL, precision: coefficient variations (CV) were less than 20% for inter-day and intra-day for both 0.1 mg/mL nimetazepam and quality control samples. In conclusion, the HPLC method intended for the detection of nimetazepam met the parameters required for routine drug analysis in forensic laboratories.